An evaluation of COVID-19 serological assays informs future diagnostics and exposure assessment - GeurtsvanKessel, Corine H.; Okba, Nisreen M. A.; Igloi, Zsofia; Bogers, Susanne; Embregts, Carmen W. E.; Laksono, Brigitta M.; Leijten, Lonneke; Rokx, Casper; Rijnders, Bart; Rahamat-Langendoen, Janette; van den Akker, Johannes P. C.; van Kampen, Jeroen J. A.; et al. (Nature communications, 2020)
The world is entering a new era of the COVID-19 pandemic in which there is an increasing call for reliable antibody testing. To support decision making on the deployment of serology for either population screening or diagnostics, we present a detailed comparison of serological COVID-19 assays. We show that among the selected assays there is a wide diversity in assay performance in different scenarios and when correlated to virus neutralizing antibodies. The Wantai ELISA detecting total immunoglobulins against the receptor binding domain of SARS CoV-2, has the best overall characteristics to detect functional antibodies in different stages and severity of disease, including the potential to set a cut-off indicating the presence of protective antibodies. The large variety of available serological assays requires proper assay validation before deciding on deployment of assays for specific applications. SARS-CoV-2 is causing a global pandemic in which the implementation of serology can support decision making in different scenarios. Here, the authors compare the outcome of eight commercially available assays to virus neutralization and discuss their use in diagnostics and exposure assessment of SARS-CoV-2.